(untitled) (The Pakistan Development Review, 2011)
The intertemporal approach has become a basic reference in open economy macroeconomics for the theoretical understanding of the current account. Since the early 1980s there has been substantial growth in the literature using this approach to analyse the behaviour of the current account movements for different countries and time periods. The theoretical refinements in the approach have led most of the empirical studies in the literature today to apply the basic present value model of current account (PVMCA) and its extended version to examine the fluctuations in the current account balances of both developed and developing countries. Using data on Pakistan over the period 1960 to 2009, the present study finds that the basic model fails to predict the dynamics of the actual current account. However, extending the basic model to capture variations in the world real interest rate and the real exchange rate significantly improves the fit of the intertemporal model. The extended model predictions better replicate the volatility of current account data and better explain historical episodes of current account imbalance in Pakistan. JEL classification: C32, F32, F41 Keywords: Current Account, Present Value Models, Consumption-based Interest Rate, Pakistan